(3Odjd JSjjQ GdeTGQjYs - (3YHO GdMejO(B, (3bGQjs ((3GdLRGFQ(B:s (3OGQ GdNdOhfjI(B,s, 2005)
-(3OQGSGJ bHd GdJWhQ,eQGMd JWhQ GdeTQhY,JWHjb GdeTQhY,GdYbhO aj GdeTGQjY GdUfGYjI,JUeje hLOhdI,JYQja GdeTQhY hJGQjNgs
Keywords: (3EOGQI GdCYeGds; (3GdeTQhYGJs